ACTIO PAULIANA SEBAGAI MODEL UPAYA HUKUM OLEH KREDITOR TERHADAP PENGALIHAN HARTA KEKAYAAN DEBITOR SEBELUM PUTUSAN PERNYATAAN PAILIT - Ismail, Jus‘an; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
In implementing bankruptcy, there is often an incident where the debtor has bad intentions which can cause losses to creditors. In the event of bankruptcy, debtors are often found doing things deliberately to avoid their responsibilities regarding debts with creditors. For example, this action is like a debtor trying to hide the assets he owns in the hope that they will not be confiscated by the court regarding payment of the debtor's obligations to creditors. In this writing, there are two problem formulations, namely regarding the legal rules governing actio pauliana in Indonesia in relation to bankruptcy events and regarding efforts to provide legal protection for creditors in connection with the existence of actio pauliana. This writing will be carried out on the basis of normative juridical research methods where library research will be used, because this type of research will be carried out on the basis of secondary materials or library materials only. Apart from that, this research will also use several principles in the field of law and legal theory. The results of the problem analysis that has been carried out are regarding the legal rules governing actio pauliana in Indonesia which are regulated in Article 1341 of the Civil Code which is a general rule and Articles 41-49 of the Bankruptcy Law and PKPU. Regarding legal protection efforts that can be provided to creditors in bankruptcy through Actio Pauliana, there are two efforts, namely preventive and repressive protection. Preventive protection efforts in the form of legal regulations regarding actio pauliana in Articles 41-49 of the Bankruptcy Law and PKPU and repressive efforts which are also related to allowing creditors to make efforts to request cancellation of the debtor's transfer of assets to third parties.Keywords: Actio Pauliana, Debtor, Creditor, Bankruptcy